2010
DOI: 10.1080/1068316x.2010.481624
|View full text |Cite
|
Sign up to set email alerts
|

Police interviews with suspected child sex offenders: does use of empathy and question type influence the amount of investigation relevant information obtained?

Abstract: Using transcripts of 26 real-life interviews with suspected child sex offenders from England, this study examined the use of empathy and the impact of question type on the amount of investigation relevant information (IRI) obtained. There were no significant differences in the amount of IRI obtained in the interviews as a function of the use of empathy by police officers. The mean proportion of inappropriate questions was significantly higher than the mean proportion of appropriate questions and, as hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
104
3
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(114 citation statements)
references
References 45 publications
5
104
3
2
Order By: Relevance
“…Grounded theory was well suited for this research because it supports the derivation of analytic categories directly from the data rather than from pre-conceived hypotheses. To date, there exists no preexisting theory to label and explain specific types of empathic behaviour displayed by police officers during interviews with sex offenders (or indeed any type of offender), and the limited amount of published research has employed a broad operational definition of empathy (see also Oxburgh & Ost, 2011;Oxburgh et al, 2012;Oxburgh et al, 2015). Given that empathy is a complex and multifaceted cognitive and social phenomenon (e.g., Jolliffe & Farrington, 2004;Larden, Melin, Holst, & Langstrom, 2006), grounded theory was employed to label types of empathy in the first instance.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Grounded theory was well suited for this research because it supports the derivation of analytic categories directly from the data rather than from pre-conceived hypotheses. To date, there exists no preexisting theory to label and explain specific types of empathic behaviour displayed by police officers during interviews with sex offenders (or indeed any type of offender), and the limited amount of published research has employed a broad operational definition of empathy (see also Oxburgh & Ost, 2011;Oxburgh et al, 2012;Oxburgh et al, 2015). Given that empathy is a complex and multifaceted cognitive and social phenomenon (e.g., Jolliffe & Farrington, 2004;Larden, Melin, Holst, & Langstrom, 2006), grounded theory was employed to label types of empathy in the first instance.…”
Section: Methodsmentioning
confidence: 99%
“…For example, females have been found to be more empathic than males (Baron-Cohen & Wheelwright, 2004), with femininity being strongly and positively correlated with empathy (Karniol, Gabay, Ochion, & Harari, 1998), a finding supported by research (Gettman, Ranelli, & Reid, 1996), which suggests gender influences behaviour and responses to others. Previous interviewing research has not yet considered gender, although Oxburgh et al (2012) did comment that suspects (who were all male) appeared to offer more 'empathic opportunities' to female interviewers than to male interviewers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bull, 2010;Davies, et al, 2000;Lamb, et al,1998;Lamb, et al, 2009;Myklebust & Bjørklund, 2006;2009;Oxburgh, Ost & Cherryman, 2010a;Oxburgh, Myklebust & Grant, 2010b;Poole & Lamb 1998). Such best practice is also promoted through investigative interviewing institutes such as the National Institute of Child Health and Human Development (NICHD; Lamb et al, 2000b).…”
Section: Questioning Stylesmentioning
confidence: 99%
“…Many have found that interviews contain mainly direct, leading and suggestive utterances (Aldridge & Cameron, 1999;Craig, et al, 1999;Davies & Wilson, 1997;Lamb, et al, 1996a;Lamb, et al, 2009;Myklebust & Bjørklund, 2006;Oxburgh et al, 2010a;Sternberg, et al, 2001).…”
Section: Questioning Stylesmentioning
confidence: 99%